Mahi Ngātahi: Culturally Responsive Ways of Working With Whānau Accessing Well Child/Tamariki Ora Services - Tipa, Zoe (Auckland University of Technology, 2021)
Well child/tamariki ora (WCTO) services in Aotearoa provide child and family health services to over 90 percent of families with children under five years of age. Feedback from Māori consumers across the health sector describes experiences of institutional racism and unconscious bias. The feedback from whānau accessing WCTO services is no different. Māori as Aotearoa New Zealand’s Indigenous people and partners to Te Tiriti o Waitangi are entitled to experience the same level of health and wellbeing as non-Māori. However, research and growing health disparities indicate that this is not the case. It is thought that by increasing health professional and organisational cultural responsiveness, Māori will be more likely to connect with WCTO services in meaningful ways and in turn, experience better health outcomes. The intent of this research was to provide a theoretical explanation for health professionals working together with Māori in a WCTO context. The study was designed to identify what matters to whānau engaging with services mandated to support families with young children. The research question was, ‘what are the processes involved for working together in a culturally responsive way with Māori accessing WCTO services?’ A kaupapa Māori methodology and constructivist grounded theory methods research design was used to develop a theory for culturally responsive WCTO services. Eighteen whānau (35 participants) with children under five were interviewed about their experiences with WCTO services. Mahi Ngātahi – a theory for culturally responsive well child/tamariki ora services was constructed which explained whānau experiences in their interactions with WCTO providers. Doing ‘to’ whānau, diminishing whānau mana and getting what whānau need were identified as core categories of the theory. Based upon this theory, Mahi Ngātahi - A cultural responsiveness framework for WCTO services was developed to depict the steps involved in providing culturally responsive WCTO services to whānau, within a whānau context. The cultural responsiveness framework outlines three stages – (1) connected, (2) included and (3) culturally safe, as the processes involved in providing culturally responsive WCTO services. The cultural competence progression of the practitioner is also identified as contributing to culturally responsive WCTO service delivery. Whānau in Aotearoa want WCTO services that they see themselves in. They want a service that meets them where they are rather than one that judges them against predetermined outcomes. This research reinforces the need for a reduction in organisational silos and highlights relationship building as fundamental to the provision of services that meet whānau needs.
Keywords: Cultural responsiveness; Cultural safety; Nursing; Kaupapa Māori; Child and family; Well child; Tamariki ora; Māori health